Around erosion of the Rule of Law: First steps of the government of Salvador Allende: between fear and controversy - Díaz Nieva, José Manuel (Derecho Público Iberoamericano, 2014)
This work deals with the first measures adopted by the government of Salvador Allende, given the particular circumstances of such historical context. All those measures pavimented the way to the –formal and material– erosion of the Rule of Law. The intolerance of ruling only for its partisan; the organization of a partisan militia for his personal safety; the grant of political asylum to supporters of subversive groups who threatened the compliance of the Rule of Law; the display of extraordinary prerrogatives to legislate, mostly without Congress’ consent; the revival of ancient and forgotten legislation, applied against its original intent; the takings of agricultural properties, by violent means; the taking of the cooper mining industry, damaging the foreign investment. All these measures, as a whole, did certainly not contribute to the democratic dialogue during such a period.